Chlorogenic acids composition and the impact of in vitro gastrointestinal digestion on espresso coffee from single-dose capsule. (August 2020) - Vilas-Boas, Ana A.; Oliveira, Ana; Jesus, Diva; Rodrigues, Carla; Figueira, Cláudia; Gomes, Ana; Pintado, Manuela
Graphical abstract: Highlights: CGAs were quantified in 11 espresso coffees from single-dose capsule. Expresso coffees have high amount of CGAs mainly, 5-CQA, 3-CQA, 4-CQA and diCQAs. CGAs from expresso coffees decrease after in vitro gastrointestinal digestion. Acid conditions decrease CGAs content while basic conditions favors isomerization. CGAs in expresso coffee still exert antioxidant activity after in vitro digestion. Abstract: The single-dose coffee capsule is the most successful technology used to prepare espresso coffee (EC). However, the characterization of ECs extracted using this technology, regarding chlorogenic acids (CGAs) composition, antioxidant activity and stability during gastrointestinal digestion (GID), are still limited. The aim of this research work was: (i) to characterize the phenolic profile and antioxidant activity of 11 commercial ECs from single-dose capsule system and (ii) to evaluate the impact of the in vitro GID on the stability of CGAs. Within all the ECs analysed it was detected the presence of 4 caffeoylquinic acids (CQAs), 1 feruloylquinic acids, 2 caffeoylshikimic acids and 3 diCaffeoylquinic acids (di-CQAs). The major compound in all ECs was 5-CQA, followed by 4-CQA and 3-CQA. The di-CQAs were found in lower concentration than CQAs (4, 5-diCQA > 3, 4-diCQA > 3, 5-diCQA). The total CQAs and diCQAs content of the ECs analyzed ranged from 1.86 ± 0.19 to 2.42 ± 0.28 and 0.26 ± 0.02 to 0.42 ± 0.06 mg/mL of EC, respectively. The high antioxidant activity of the ECs is related with the high CGAs concentration, which ranged from 4.92 ± 0.29 to 7.28 ± 0.25 mg AAE/mL of EC and from 6.13 ± 0.37 to 10.07 ± 0.17 mg TE/mL of EC for ABTS° and DPPH° methods, respectively. The principal component analysis showed that the coffee variety used in ECs preparation explained 74.8% of the results' variation and that 6 of the total number of ECs were related with high CGAs contents and antioxidant activity. The GID induced a decrease in most CGAs, which had a direct impact on the antioxidant activity, therefore concerning EC ingestion the CGAs bioaccessible concentration decreased in comparison with a non-digested EC. Nevertheless, the CGAs concentration available after GID is still sufficiently high to exert antioxidant activity (measured in vitro ) that may exert a potential beneficial effect on humans health.